Bioanalytical evaluation of Lactobacillus delbrueckii subsp. lactis 313 cell-envelope proteinase extraction - Agyei, D.; Lim, W.; Zass, M.; Tan, D.; Danquah, Michael (Pergamon, 2013)
Lactobacilli cell-envelope proteinases (CEPs) have demonstrated numerous biopharmaceutical applications in the development of new streams of blockbuster nutraceuticals; thus, the development of efficient and commercially viable methods for CEP extraction will promote their full-scale application. In this study, the sub-cellular location of CEPs in Lactobacillus delbrueckii subsp. lactis 313 (LDL 313) was identified and the effects of different extraction methods were investigated for their ability to efficiently release CEPs from LDL 313. Significantly high relative proteinase activity of~95% was detected in cell-wall fractions and ~5% activity was observed for osmotic fluids, implying that proteinases in LDL 313 are cell-wall bound. CEPs were released from cell-wall via incubation in calcium-free buffer, indicating the enzyme is liable to self-digestion and ionic misfolding. Of the different extraction methods investigated, the use of 5. M LiCl was the most suitable, under the conditions of experimentation, for releasing high levels of CEPs from LDL 313.